Critical Discourse Analysis Norman Fairclough on ASN Social Movements in the Instagram Community @abdimuda_id - Asti Prasetyawati (Universitas Indraprasta PGRI, 2021)
Civil Servant in Indonesia (ASN) has a bad stigma in society. This could decrease the level of public trust in ASN as well as the confidence level of young ASN for their profession. Based on these problems, various movement communities which called themselves as young ASNs were formed, one of which was the Abdimuda Indonesia (@abdimuda_id). As a movement community, Abdimuda Indonesia formed as a medium for young ASN from all regions in Indonesia to jointly develop themselves and maintain positive idealism in order to break down the negative stigma of ASN that already exists. Through Norman Fairclough's Critical Discourse Analysis (CDA) and Barthes' semiotic analysis, this qualitative study wanted to analize the text cracks which formed from framing alignment behind the discourse of ASN in @abdimuda_id. The results indicate that contents uploaded by @abdimuda_id has a tendency to reflect positive values related to ASN which used by Abdimuda Indonesia to do social change and transforming the negative stigma of ASN into a better image.Keywords: Movement community, framing alignment, critical discourse analysis, semiotics, Abdimuda Indonesia